A comprehensive review of production and utilisation of ammonia as potential fuel for compression ignition engines - Jaffar Hussain; Marutholi Mubarak; Duraisamy Boopathi; Ravikumar Jayabal (Next Sustainability, 2025)
For centuries, internal combustion engines (ICEs) have powered cars using gasoline and diesel as the primary fuel. Bio-derived fuels have been blended with conventional fuels to address the depletion of fossil fuels and their associated greenhouse effect. The researchers focus on finding new technology that leads to carbon-free mobility. Renewable energy sources such as ammonia, hydrogen, and CNG are becoming increasingly popular as efficient substitutes for traditional fuels. Due to the concern about the production and storage of hydrogen, ammonia is gaining momentum due to its better hydrogen-storing capacity. This review paper aims to discuss the various ammonia production processes, the possibilities of ammonia as fuel in conventional CI engines, and the use of ammonia in internal combustion engines. Research has shown that the addition of ammonia to CI enhances its performance, and the use of dual fuel can boost the output's economic efficiency. However, it is important to note that this approach may also lead to increased NOₓ emissions. Some of the most important things that the review showed were that ammonia works well in dual fuel mode, 40–60 % diesel fuel energy is needed for maximum fuel efficiency, and NO emissions go down if ammonia replaces less than 40 % of the energy. For this reason, ammonia could potentially serve as a fuel for CI engines, leading to improved performance and a reduction in NOₓ emissions.